AUREL STROE - LE CONCERT POUR ACCORDÉON ET ENSAMBLE DE SOLISTES: CONSIDÉRATIONS SÉMANTIQUES - COROIU, Petruța-Maria (Studia Universitatis Babes-Bolyai Musica, 2020)
An avant-garde composer, a great thinker on the musical and musicological phenomenon, the possessor of interior images that give birth to music of a particular beauty, Aurel Stroe was also a teacher of the Bucharest Conservatory until he left the country, settling in Germany. His music has a great complexity, bordering on different artistic and conceptual routes, characterized by multidisciplinarity and multiculturalism. The concert for accordion and ensemble of soloists is his last major work and concentrates the synthesis of his compositional and semantic resources (especially the third part, Accord-matrice). The matrix accord coagulates the tensions that have occurred in the concert and succeeds with a unique ability to reduce the expressive field of the preceding elements into a single structure.